Microstructure and Mechanical Properties of Thick‐Walled Inconel 625 Alloy Manufactured by Wire Arc Additive Manufacture with Different Torch Paths. Issue 1 (16th September 2020) - Jiang, Qi; Zhang, Peilei; Yu, Zhishui; Shi, Haichuan; Li, Shaowei; Wu, Di; Yan, Hua; Ye, Xin; Chen, Jieshi
Abstract : Wire arc additive manufacture (WAAM) technology has attracted more and more attention. WAAM technology provides a way to manufacture a large‐scale part at a low cost and with less material loss. Inconel 625 alloys are widely used for their excellent mechanical properties and corrosion resistance. Therefore, it is important to investigate the performance of Inconel 625 alloy in WAAM. Herein, cold metal transfer (CMT) arc is used as the heat source to fabricate thick‐walled parts of Inconel 625 alloy by WAAM, and study the difference between microstructure and mechanical properties under the different torch trajectories. The result shows that the grains inside the parts are all thick dendrites and show the trend of epitaxial growth. The thermal input of the oscillation additive is higher than the two‐pass multilayer additives, and the Laves phase also precipitated more. The maximum tensile strength occurs in parallel sampling close to the substrate, which is 693.5 ± 12.6 and 751.2 ± 17.6 MPa in oscillation and two‐pass multilayer modes, respectively. The maximum elongation is obtained in the vertical direction is 60 ± 1.0% and 60 ± 1.1%. The anisotropies are 4% and 4.5%, respectively. The maximum hardness value under the two torch trajectories also appears close to the substrate. Abstract : Herein, two welding torch paths are used to produce the parts. The maximum tensile strength occurs in parallel sampling close to the substrate, which is 693.5 ± 12.6 and 751.2 ± 17.6 MPa in oscillation and two‐pass multilayer modes, respectively. The maximum elongation is obtained in the vertical direction is 60 ± 1.0% and 60 ± 1.1%. The anisotropies are 4% and 4.5%, respectively.